A verticalização das mulheres em profissões vistas socialmente como masculinas no Instituto Federal de Mato Grosso do Sul, Campus de Corumbá - Gianvecchio, Larissa Angelini de Andrade (2022)
Gender relations are present in the social, educational, and professional spheres; historically, the sexual division of labor has predominated in society. In such a manner, the research aimed to investigate how the verticalization of women in professions socially seen as masculine occurs at the Federal Institute of Mato Grosso do Sul (IFMS), Campus of Corumbá, Brazil, according to the perspective of lecturers and pupils of the Integrated Technician in Metallurgy (High School) and Technology in Metallurgical Processes (Higher Education) courses. The theoretical framework is based on gender studies, from post-structuralist feminist approaches, and includes discussions on patriarchy, feminist movements and struggles, and the sexual division of labor, among other topics. For the field research, a survey of quantitative data was carried out by the secretary of the IFMS Campus de Corumbá to identify the proportion between women and men in the courses: Integrated Technician in Metallurgy (classes of 2015 to 2018 that were concluded between 2018 and 2021); and Technology in Metallurgical Processes (classes of 2015 and 2016 that were concluded in 2020 and 2021). In addition, recordings of individualized interviews were carried out through the Google Meet platform with three students and two teachers of the aforementioned courses, two of the interviewees were already in the process of verticalization, while one student rejected the possibility of verticalizing for the course of Metallurgical Process Technology. The results of the empirical research indicate that women who choose to work in this area of metallurgy face many difficulties both in their education and professional scope, particularly because they are female. Amid the research, another social marker emerged: the racial issues, which pointed out that women are not on an equal footing, since black women have their difficulties potentiated by the simple fact of being black. As for the IFMS (Campus of Corumbá), it is evident that it is a democratic educational institution, that seeks to break with the barriers imposed by society, because in addition to allowing women to enter all areas of knowledge, the institution encourages them to participate in scientific research and to enter the field of exact sciences, thus breaking with some paradigms that were once established. Finally, it is noteworthy that research such as this present work effectuated in the Masters in Education course at the UFMS (Campus of Pantanal) can contribute to the reduction of prejudice and discrimination in the field of work, especially when it comes to female performance in professions seen socially as masculine. Keywords: Verticalization of Women. Sexual Division of Labor. Gender relations. Professional Choice.